(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In the following pages, we evaluate a brief assessment in to the concept and characteristics of the tax liability as well as its degree of difference in respect to the Civiland Administrative responsibilities, the procedure of derivation of tax liability,examining the different phases that culminate with the declaration of responsibility and that are necessary to transmit the liability of the tax debt to individuals that are unfamiliar to the taxable right emphasizing the fundamental guarantee of the principles of the Responsibilities, upon increasing the amount of subjects that are responsible for the tax, not currently exempt of a sanctioned character.These characters, combined with the operations which have to be realized in the procedure of the derivation process (which make to this procedure to get close tothe tax clearance procedure), established it as an autonomous process within there covery process of the tax collection law. We continue to examine the features that are presented by the process in respect of the severally liable and the vicariously liable, basically the requirement for the vicariously liable of a previous statement of failure from the principal debtor and these verally liable, and hence the different timeframe in which one or some other responsible can be declared. In conclusion we discuss the consequences for the principal debtor what stems in the payment made by the responsible, who has the express legal recognition of the right of reimbursement against the principal debtor, that occur, in concept, with the debts that are not objects of derivation, as an example the pressure of surcharges.